Dynamics of Legal Politics and Power Contestation after Constitutional Court Decision Number 60/PUU-XXII/2024 Concerning the Wholesale Party System in the 2024 Simultaneous Regional Elections - Yudhistira, Dhieno; Santiago, Faisal (Greenation Publisher & Yayasan Global Resarch National, 2025)
Constitutional Court Decision Number 60/PUU-XXII/2024 has become a critical turning point in the Indonesian legal political landscape, especially regarding the political party system in the implementation of the 2024 Simultaneous Regional Elections. This decision cancels the practice of